2022
DOI: 10.3389/fnhum.2022.907425
|View full text |Cite
|
Sign up to set email alerts
|

Through Thick and Thin: Baseline Cortical Volume and Thickness Predict Performance and Response to Transcranial Direct Current Stimulation in Primary Progressive Aphasia

Abstract: ObjectivesWe hypothesized that measures of cortical thickness and volume in language areas would correlate with response to treatment with high-definition transcranial direct current stimulation (HD-tDCS) in persons with primary progressive aphasia (PPA).Materials and MethodsIn a blinded, within-group crossover study, PPA patients (N = 12) underwent a 2-week intervention HD-tDCS paired with constraint-induced language therapy (CILT). Multi-level linear regression (backward-fitted models) were performed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 116 publications
0
3
0
Order By: Relevance
“…A combined approach with tDCS and cognitive and behavioral training appears to be more effective than stimulation alone (Cappelletti et al, 2013 ; Martin et al, 2014 ; Mancuso et al, 2016 ). Strengthening or weakening activation patterns via Hebbian synaptic mechanisms of neuroplasticity, as suggested neural mechanisms of tDCS, can be selectively reinforced by external stimulation, such as cognitive training, speech therapy, motor, attention, and WM training (Jones et al, 2015 ; Wang et al, 2018 ; Boroda et al, 2020 ; Nissim et al, 2020 , 2022 ). For this reason, we suggest potential frameworks and approaches for the practical implementation of tDCS projects in DS that combine tDCS and cognitive and behavioral training, aimed at improving cognition and behavior.…”
Section: Hypothesis Of Tdcs Treatment Application In Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…A combined approach with tDCS and cognitive and behavioral training appears to be more effective than stimulation alone (Cappelletti et al, 2013 ; Martin et al, 2014 ; Mancuso et al, 2016 ). Strengthening or weakening activation patterns via Hebbian synaptic mechanisms of neuroplasticity, as suggested neural mechanisms of tDCS, can be selectively reinforced by external stimulation, such as cognitive training, speech therapy, motor, attention, and WM training (Jones et al, 2015 ; Wang et al, 2018 ; Boroda et al, 2020 ; Nissim et al, 2020 , 2022 ). For this reason, we suggest potential frameworks and approaches for the practical implementation of tDCS projects in DS that combine tDCS and cognitive and behavioral training, aimed at improving cognition and behavior.…”
Section: Hypothesis Of Tdcs Treatment Application In Down Syndromementioning
confidence: 99%
“…The potential of this approach lies in its ability to improve functioning by addressing altered E/I balance and neuroplasticity (Bavelier et al, 2010 ). By strengthening or weakening activation patterns through Hebbian synaptic mechanisms of neuroplasticity, tDCS may modulate external stimulation, such as cognitive, speech and motor training, selectively reinforcing their effects (Jones et al, 2015 ; Wang et al, 2018 ; Boroda et al, 2020 ; Nissim et al, 2020 , 2022 ).…”
Section: Concluding Remarks and Future Direction Of Researchmentioning
confidence: 99%
“…Recent studies from different groups, including our own, have identified several baseline factors that predict efficacy of tDCS for a given patient or patient group [see [6][7][8] for reviews]. Five predictive factors have been identified: (1) baseline language and cognitive performance [9,10], (2) baseline cortical volume and thickness [11][12][13], (3) baseline white matter integrity [14], (4) clinical variant PPA [15], and (5) baseline sleep efficiency [16]. To our knowledge, no studies have utilized baseline functional brain connectivity as a predictor of tDCS effects in PPA.…”
Section: Introductionmentioning
confidence: 99%